Tinjauan Hukum Pengaturan PPPK Paruh Waktu dan PPPK Penuh Waktu serta Dampaknya Terhadap Hak dan Kewajiban Pegawai - Varik Farsyak; Muhammad Adrian Fitra Yamazaki; Aldo Kurniawan; Iskandar; Madinar (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
This study aims to analyze the provisions of part-time and full-time Government Employees with Employment Agreements (PPPK) in the Indonesian civil service legal system and examine the legal implications of the differences in rights and obligations between the two. The research method used is normative legal research with a statutory and conceptual approach, utilizing primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that full-time PPPK have a clear regulatory basis in laws and regulations, specifically in Law Number 20 of 2023 concerning the State Civil Apparatus and Government Regulation Number 49 of 2018. Meanwhile, part-time PPPK do not have explicit normative regulations, resulting in legal uncertainty. This difference has implications for an imbalance in rights and obligations, particularly regarding salaries, benefits, job protection, and certainty of tenure. This condition has the potential to cause injustice and contradicts the principle of legal certainty and the merit system in ASN management. Therefore, regulatory harmonization is needed to ensure justice, legal certainty, and protection of the rights of all PPPK.